2005
DOI: 10.1523/jneurosci.0920-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Impairments in Patients with Unilateral Cerebellar Lesions Are Selective to Inputs from the Contralesional Nostril

Abstract: Functional imaging studies of olfaction have consistently reported odorant-induced activation of the cerebellum. However, the cerebellar role in olfaction remains unknown. We examined the olfactory and olfactomotor abilities of patients with unilateral cerebellar lesions, comparing performance within subjects across nostrils, as well as between subjects with age-matched and young controls. Regarding olfactory performance, initial testing revealed that patients had a contralesional impairment in olfactory ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 52 publications
7
47
0
Order By: Relevance
“…Thus, this olfactory-spinal path could also activate the cerebellum in the rat. The existence of such a pathway in humans and other animal models is supported by studies that consistently found activation of the cerebellum by stimulation of the olfactory system [27,28]. Here we showed that distant stimulation with sexual cues seems to produce a similar effect in male rats.…”
Section: Discussionsupporting
confidence: 78%
“…Thus, this olfactory-spinal path could also activate the cerebellum in the rat. The existence of such a pathway in humans and other animal models is supported by studies that consistently found activation of the cerebellum by stimulation of the olfactory system [27,28]. Here we showed that distant stimulation with sexual cues seems to produce a similar effect in male rats.…”
Section: Discussionsupporting
confidence: 78%
“…Olfactory perceptual impairments in patients with unilateral cerebellar lesions are found to be selective to nasal inputs on the side opposite the cerebellar lesion. 162 The results provide further evidence for an olfactocerebellar pathway and suggest that this pathway connects each nostril primarily to the contralateral cerebellum. The ability of a sniff to adjust odour sampling depending on odorant concentration and familiarity is thus seen to be an integral part of the olfactory percept.…”
Section: Active Sampling and Olfactory Perceptionsupporting
confidence: 52%
“…alterations in olfactomotor processing in diseases such as Parkinson's disease (Sobel et al, 2001) or after lesions to candidate components of the olfactomotor system such as the cerebellum (Mainland et al, 2005). Although sniffing may be considered an inseparable part of the olfactory percept (Kepecs et al, 2006;Mainland and Sobel, 2006;Schoenfeld and Cleland, 2006), it is nevertheless subserved by an independent olfactomotor system (Sobel et al, 1998).…”
Section: Discussionmentioning
confidence: 99%